Determination of Isoproturon in Environmental Samples using the QuEChERS Extraction‐Spectrofluorimetric Method. (16th November 2019) - Muhammad, Mian; Rasul Jan, Muhammad; Shah, Jasmin; Ara, Behisht
Abstract: An accurate and sensitive method has been developed for determination of the herbicide isoproturon using the Quick Easy Cheap Effective Rugged Safe (QuEChERS) extraction‐spectrofluorimetric technique. The method involves the reaction of 2‐cyanoacetamide with isoproturon in basic medium (NH3 ; 15 mol/L). The resulting fluorescent product was found to show maximum emission at 378 nm and maximum excitation at 333 nm. Fluorescence intensity under the influence of different parameters was investigated. The linear range of analyte concentrations was found to be 0.5 to 15 µg/mL, with a limit of detection of 0.144 µg/mL, a limit of quantification of 0.437 µg/mL (signal to noise ratio = 3), and a regression coefficient of 0.9991, under optimized conditions. The proposed method was effectively applied for determination of isoproturon in different matrices; the percentage of recovery varied from 85.00 ± 1.2% to 96.00 ± 0.5%. The method was also applied for residue analysis of isoproturon in real soil samples collected from a pilot field. For extraction of isoproturon, the QuEChERS extraction approach was used, and the average residue in the soil samples was found to be 0.81 ± 0.07 µg/g. To show the potential of this approach, our results were compared with those of other methods reported in the literature. Environ Toxicol Chem 2019;38:2614–2620. © 2019 SETAC